Microclimate Field Measurement in Melaka Waterbodies - Manteghi, Golnoosh; Mostofa, Tasneem; Hanafi, Zulkifli (International Journal of Engineering and Technology, 2018)
This research will help to develop an understanding of the existing waterbodies environmental conditions in Melaka Town.  There are 2 necessary tests that need to be conducted to comprehend the characteristics of the Melaka River and the sea and their impact to the surrounding microclimate.  The climate data includes air temperature (Ta), relative humidity (RH) and wind velocity (v), which were all continuously measured within the Melaka water body area.  The study measures the microclimate condition within a number of stations, quantified by their respective distances within the sea and the river area respectively.  This measurement activity seeks to provide an understanding in the field of climatic urban design, and the potential of utilizing water bodies (water cooling effects), as an urban design tool, with regard to minimise the profound effects of extreme climate condition on human comfort levels under hot and humid condition in Melaka Town. On a clear day, temperatures in surrounding area increase by 0.25 to 0.30 °C approximately 25 meters away from the water bodies. The findings could be used to determine how the surroundings near the water bodies affect the water bodies’ cooling effect performance.